The Influence of Corporate Social Responsibility on Supply Chain Management - Kaźmierczak , Magdalena (Studia Oeconomica Posnaniensia, 2016)
In recent years, an increased interest in the concept of CSR (Corporate Social Responsibility) has been observed, as well as, although to a lesser extent, in the concept of sustainable supply chain management (SSCM). With the increase in awareness of corporate social responsibility, the conviction of companies that supply chains and efficient management of today determine their market success grows as well, as it is a valuable daily source of information about themselves and values. The purpose of this paper is to give a brief presentation of both the concept and attempt to answer the questions: what are the relationships between them? How does CSR influence the management of the supply chain? How can one take full advantage of the knowledge that comes from both of these areas to ensure a stable future for organizations and their supply chains, workers and the environment in which they operate? In the first part of the article, the essence of CSR is described. The second part presents the essence of the supply chain and the concept of sustainable supply chain management. Furthermore, in the third part, examples of CSR in supply chain management are discussed.